2014
DOI: 10.1039/c4dt00467a
|View full text |Cite
|
Sign up to set email alerts
|

Lithium recovery from salt lake brine by H2TiO3

Abstract: The details of the ion exchange properties of layered H2TiO3, derived from the layered Li2TiO3 precursor upon treatment with HCl solution, with lithium ions in the salt lake brine (collected from Salar de Uyuni, Bolivia) are reported. The lithium adsorption rate is slow, requiring 1 d to attain equilibrium at room temperature. The adsorption of lithium ions by H2TiO3 follows the Langmuir model with an adsorptive capacity of 32.6 mg g(-1) (4.7 mmol g(-1)) at pH 6.5 from the brine containing NaHCO3 (NaHCO3 added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
129
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(140 citation statements)
references
References 30 publications
6
129
1
4
Order By: Relevance
“…In addition, manganese ions in the adsorbent are dissolved out during regeneration, restricting the reuse of the adsorbents (Nishihama et al, 2011;Shi et al, 2011). Recently, in order to improve the adsorption process, several trials were reported by introducing better fabrication methods (Xiao et al, 2012(Xiao et al, , 2013, proposing a new desorption method (Ryu et al, 2013a), applying reducing agents (Intaranont et al, 2014), or using a novel adsorbent (Chitrakar et al, 2014). …”
Section: Introductionmentioning
confidence: 98%
“…In addition, manganese ions in the adsorbent are dissolved out during regeneration, restricting the reuse of the adsorbents (Nishihama et al, 2011;Shi et al, 2011). Recently, in order to improve the adsorption process, several trials were reported by introducing better fabrication methods (Xiao et al, 2012(Xiao et al, , 2013, proposing a new desorption method (Ryu et al, 2013a), applying reducing agents (Intaranont et al, 2014), or using a novel adsorbent (Chitrakar et al, 2014). …”
Section: Introductionmentioning
confidence: 98%
“…[20] Actually,t he high demand for Li as ar esult of electric car batteries is already driving scientists to find more effective methods to extract Li from brine [35] or even seawater; [36] it has been proven that there are 230 billion tons of Li in seawater. For instance,t heoretically,4kg of Li ions from 3-30 m 3 Li-rich brine can fully prelithiate 4kgo fS i, which could be used for one electricalc ar.…”
Section: à2mentioning
confidence: 99%
“…Chitrakar et al. found that the adsorption capacity of H 1.33 Mn 1.67 O 4 and H 1.6 Mn 1.6 O 4 reached up to 30.0 mg g −1 . Furthermore, the crystal structure of LMO only matches the size of Li + , giving a distinct “lithium ion‐sieve effect,” that is, the large‐sized Na + , K + , and Ca 2+ cannot enter.…”
Section: Introductionmentioning
confidence: 99%